2012
DOI: 10.1002/da.21925
|View full text |Cite
|
Sign up to set email alerts
|

ELEVATED tph2 mRNA EXPRESSION IN A RAT MODEL OF CHRONIC ANXIETY

Abstract: Background Allelic variations in TPH2, the gene encoding tryptophan hydroxylase 2, the rate-limiting enzyme for brain serotonin (5-HT) biosynthesis, may be genetic predictors of panic disorder and panic responses to panicogenic challenges in healthy volunteers. To test the hypothesis that tph2 mRNA is altered in chronic anxiety states, we measured tph2 expression in an established rat model of panic disorder. Methods We implanted 16 adult, male rats with bilateral guide cannulae and then primed them with dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 97 publications
4
33
0
Order By: Relevance
“…No. 74104, Qiagen, Valencia, USA), and used in an ISHH assay as described previously (Donner and Handa, 2009; Donner et al, 2012). To detect slc6a4 mRNA, a synthetic 50-base antisense oligonucleotide (5′-ACT GCA GAG TAC CCA TTG GAT ATT TGG CTA GGC TCT GCC CTG TCC GCT GT-3′, Integrated DNA Technologies, Coralville, IA, USA), complementary to bases 207–256 of rat slc6a4 mRNA (previously reported as bases 77–126 Fujita et al, 1993; Hansen and Mikkelsen, 1998), based on the published sequence of the rat serotonin transporter cDNA clone (Blakely et al, 1991) of slc6a4 mRNA ( Rattus norvegicus solute carrier family 6 (neurotransmitter transporter, serotonin), member 4, mRNA; GenBank Accession no., NM_013034.3) was used as previously described (Gardner et al, 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…No. 74104, Qiagen, Valencia, USA), and used in an ISHH assay as described previously (Donner and Handa, 2009; Donner et al, 2012). To detect slc6a4 mRNA, a synthetic 50-base antisense oligonucleotide (5′-ACT GCA GAG TAC CCA TTG GAT ATT TGG CTA GGC TCT GCC CTG TCC GCT GT-3′, Integrated DNA Technologies, Coralville, IA, USA), complementary to bases 207–256 of rat slc6a4 mRNA (previously reported as bases 77–126 Fujita et al, 1993; Hansen and Mikkelsen, 1998), based on the published sequence of the rat serotonin transporter cDNA clone (Blakely et al, 1991) of slc6a4 mRNA ( Rattus norvegicus solute carrier family 6 (neurotransmitter transporter, serotonin), member 4, mRNA; GenBank Accession no., NM_013034.3) was used as previously described (Gardner et al, 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…First, we have shown that amygdala priming (using 5 × daily bilateral infusions of 6 fmol urocortin 1 into the BL) in male rats, which results in a chronic anxiety-like state as measured in the social interaction test, resulted in increased expression of tph2 , encoding Tph2, the rate-limiting enzyme in biosynthesis of serotonin, selectively in the DRVL/VLPAG serotonergic neurons and the caudal DRV serotonergic neurons (which have also been shown to project to the DPAG (Stezhka and Lovick, 1994;Vertes, 1991)), but not in any other subdivision of the DR (Donner et al, 2012). In addition, tph2 mRNA expression was highly correlated with anxiety-like behavior in the social interaction test ( r = 0.729; p = 0.001) (Donner et al, 2012). Second, we have shown that social defeat increases tph2 mRNA expression, but only in the DRVL/VLPAG serotonergic neurons, and only in rats previously exposed to maternal separation (Gardner et al, 2009).…”
Section: The Drvl/vlpag Serotonergic System a Critical Node In Pamentioning
confidence: 99%
“…Priming of the BLA, a structure critical for processing fear-related stimuli and gating output of the CE (Adolphs, 2013;LeDoux et al, 1988), by repeated urocortin 1 (UCN1) injections increases anxiety-like behavior and elevates tph2 mRNA in the DRVL/VLPAG (Donner et al, 2012). Microinjection of urocortin 2 (UCN2), a neuropeptide in the CRH family and a selective CRHR2 agonist, directly into the DR activates serotonergic neurons and increases extracellular 5-HT in DR projection regions like the BLA (Amat et al, 2004).…”
Section: Neuropeptide Modulation Of the Panic Inhibition Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…After dehydration and coverslipping, sections were photographed under identical camera settings. The outlines of two evenly spaced sections from each animal were manually traced, and their optical density (OD) was measured using NIH ImageJ while control-ling for background color and threshold levels (15,16). OD measurements of two sections from a single animal were averaged to obtain a value for that animal.…”
Section: Testicular Cyp17a1 Icc and Analysismentioning
confidence: 99%